Towards the development of the supply chain of concentrated solar power - Tjahjono, Benny; Martinez-Conde Moreno, Javier; Tonnellier, Xavier; Schaeffer, Roberto; Portugal-Pereira, Joana (International Federation of Logistics and SCM Systems, 2016)
This work focuses on the investigation into the planning of renewable energy power plants in Brazil using the Concentrated Solar Power (CSP) technology. The main aim of the paper is to present an analysis of the planning process that can be used as a basis of the development of a method to assess the Brazilian’s local manufacturing and supply chain capabilities in supporting the deployment of the CSP technology. The paper identifies areas in which the concerted efforts should be emphasized. For this, the paper will first discuss the key components of the chosen CSP technology (in this case the parabolic through). The manufacturing processes of these components will subsequently be analyzed and the key enabling technologies will be determined. The demands of electricity will be estimated using the System Advisory Model®, a modelling tool developed by the National Renewable Energy Laboratory (NREL). An assessment method will finally be proposed to identify the potentials of the local Brazilian supply chain, through the readiness evaluation of the key enabling technologies and manufacturing processes.
Keywords: Energy Supply Chain; Concentrated Solar Power; Manufacturing Readiness; Supply Chain; System Advisory Model